Richard Castle's A calm before Storm : a Derrick Storm mystery - Castle, Richard (Marvel Worldwide, 2013)
As international situations continue to degrade, Derrick Storm turns to his former handler, Clara Strike, to help him prevent World War III as he faces the Fear in battle.